Pengaruh Kerapatan Populasi Tanaman Sela dan Mulsa Plastik terhadap Pertumbuhan dan Produksi Jagung - Wahyu Widiyono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Research of plant population density and intercropping of pigeon pie (Cajanus cajan L.) Millsp. and plastic mulching on maize were carried out in field research of R and D Centre for Biology, Indonesian Institute of Sciences, Cibinong from October 2008 to Februari  2009. The aim was to examine the effects of  plant population density and intercropping, as well as mulching to the growth and yield of maize. The resultas showed that population density, intercropping and mulching affected the maize vegetative growth. However, the maize yield was not influenced by population density; but was influenced by intercropping and mulching. Mulching increased maize production, but intercropping by using C. cajan decreased production.